2016
DOI: 10.1523/jneurosci.0206-16.2016
|View full text |Cite
|
Sign up to set email alerts
|

SNX27 and SORLA Interact to Reduce Amyloidogenic Subcellular Distribution and Processing of Amyloid Precursor Protein

Abstract: Proteolytic generation of amyloidogenic amyloid ␤ (A␤) fragments from the amyloid precursor protein (APP) significantly contributes to Alzheimer's disease (AD). Although amyloidogenic APP proteolysis can be affected by trafficking through genetically associated AD components such as SORLA, how SORLA functionally interacts with other trafficking components is yet unclear. Here, we report that SNX27, an endosomal trafficking/recycling factor and a negative regulator of the ␥-secretase complex, binds to the SORLA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
59
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 39 publications
5
59
0
Order By: Relevance
“…While no significant changes were found in the proteases involved in its cleavage, TPT-treated mice had a significant reduction in the BACE-1-derived products sAPPβ and CTF-β, suggesting that the effect on Aβ levels were secondary to a decreased proteolytic action of BACE-1 on APP. We also observed that treated mice with TPT had an increase of SorLA, an important protein implicated in APP transport from the endosome to the Golgi [27]. While we do not know the exact mechanism underlying this biological effect, we speculate that it is most likely secondary to the increased levels of VPS35.…”
Section: Discussionmentioning
confidence: 79%
“…While no significant changes were found in the proteases involved in its cleavage, TPT-treated mice had a significant reduction in the BACE-1-derived products sAPPβ and CTF-β, suggesting that the effect on Aβ levels were secondary to a decreased proteolytic action of BACE-1 on APP. We also observed that treated mice with TPT had an increase of SorLA, an important protein implicated in APP transport from the endosome to the Golgi [27]. While we do not know the exact mechanism underlying this biological effect, we speculate that it is most likely secondary to the increased levels of VPS35.…”
Section: Discussionmentioning
confidence: 79%
“…Insofar, all genetic mutations identified in SNX27 or retromer in humans have been linked to severe neuropathologies including Alzheimer’s disease [83], Parkinson’s disease [84, 85], Down syndrome [86] and infantile epilepsy [87] for recent reviews see [88, 89]. Accordingly, lowered expression of SNX27 or retromer reduces the surface cell levels of several cargo known to influence synaptic neurotransmission (N-methyl-D-aspartate receptors; NMDARs [90] and AMPARs[91], neuronal signaling and excitably (β 2 AR [90], GIRK2a [92] mGLuR5 [93]), glial cell differentiation (GPCR 17; GPR17 [94]) and, more recently, limiting the distribution of amyloid precursor protein (APP), a precursor linked to the onset and progression of Alzheimer’s disease [95]. Recent assessment of several mouse models has further extended the physiological contribution(s) of the ASRT complex to peripheral systems [96], such as the skeleton [50, 97].…”
Section: Figurementioning
confidence: 99%
“…Conversely, overexpression of SNX27 enhanced distribution of A␤PP and SORL1 to the cell surface. An increase in A␤PP protein levels at the cell surface also resulted in increased ␣-secretase cleavage of A␤PP to give sA␤PP␣ [106]. However, SNX27 has been shown to interact with PSEN1 protein and this appears to reduce ␥-secretase activity (i.e., reduced cleavage of A␤PP and Notch) [107] so this could also explain the increased levels of sA␤PP␣.…”
Section: Sorl1 and A␤ppmentioning
confidence: 99%